TINJAUAN YURIDIS TERHADAP PELAKSANAAN PRAKTIK MANDIRI BIDAN DI KOTA SAMARINDA (BERDASARKAN PERMENKES NO. 28 TAHUN 2017 TENTANG IZIN DAN PENYELENGGARAAN PRAKTIK BIDAN) - Abdi Muhammad Sasongko (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTThis study aims to know and understand how the implementation of Midwife Independent Practice in Samarinda city based on the Regulation of the Minister of Health (PerMenKes) Number 28 the Year 2017 About the License and Implementation of Midwife Practice. This study also aims to determine how the implementation of midwife health services to patients in accordance with applicable provisions. This study was conducted in Samarinda. The object of research is the City Health Office of Samarinda and three (3) Independent Practice Midwives who operate in the city of Samarinda. This research uses sociological empirical research method that is data collection of Independent Practices Midwives all of Samarinda city in Samarinda City Health Office and data collection, interview and direct observation in three (3) Independent Practice Midwives operating in Samarinda city. The results of this study indicate that in the permit and implementation of self-employment midwives in the city of Samarinda running well in accordance through the mechanism and procedure of Regulation of the Minister of Health (PerMenKes) no. 28 the Year 2017. But from the rules that have been determined there are still some violations that occurred in the field found by the author through research conducted is the requirement of self-employment midwife is not met and the services performed do not match the authority possessed by a midwife.